Hidden riches - Jenkins, Jerry B.; Fabry, Chris, 1961- (Carol Stream, Ill. : Tyndale House, 2006)
While Bryce investigates who has framed their friend Boo for robbery, twin sister Ashley tries to find the previous owner of a painting, which had a map and a large amount of cash hidden in back.
3.9
3-6
Keywords: Christian life -- Juvenile fiction; Crime -- Juvenile fiction; Twins -- Juvenile fiction; Christian life -- Fiction; Crime -- Fiction; Mystery and detective stories; Twins -- Fiction; Christian life -- Fiction; Mystery fiction; Twins -- Fiction; Colorado -- Juvenile fiction; Colorado -- Fiction; Colorado -- Fiction; Christian fiction; Mystery fiction